BEBERAPA FAKTOR RISIKO PENYAKIT GUDIKAN (SCABIES) DI PONDOK PESANTREN BINAUL UMMAH DESA BAWURAN, PLERET, BANTUL TAHUN 2018 - Ubaidillah Ubaidillah; Nikmatul Khoiriah (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2020)
Backgraund : Islamic Boarding Schools are Boarding Islamic schools where students usually stay with freinds in one room. Living with a group of people such as in a boarding schools is at risk of easily contracting various diseases including scabies. Scabies is less noticed in islamic boarding school so that it can cause health problem that result from unhealthy behaviour in maintaining personal hygiene.Objective : to determine the factors correlation with the incidence of scabies in islamic boarding schools Binaul Ummah Village Bawuran, Pleret, Bantul.Method : The design of this study is an analytical survey with a case control design. The sampel of the study was 100 in the islamic boarding schools Binaul Ummah by using Purposive Sampling. Data collection using a knowledge, personal hgyiene, density of residential questionnaires. Data analysis using Chi-Square.Result : the results of data analysis showed that knowledge is not correlation to the incidence of scabies P = 0,391, OR = 0,691. Clothes hygiene is correlation with the incidence of scabies P = 0,043. Hand an nail hygiene is correlation with the incidence of scabies P = 0,010. The cleanliness of the bed is correlation to the incidence of scabies P = 0,097. Occupancy density has correlation to the incidence of scabies P = 0,019.Conclusion : There is no correlation of knowledge with the incidence of scabies, there is a correlation between the cleanliness of clothes, hand and nail hygiene, cleanliness of the bed with the incidence of scabies and there is correlation residential density and incidience of scabies.Keyword : Scabies, Kwoledge, personal Hygiene,occupancy density